Potential limitations of biogenic silica as an indicator of abrupt climate change in Lake Baikal, Russia - Swann, George E.A.; Mackay, Anson W. (Springer, 2006)
Biogenic Silica (BSi) has been one of the most important proxies for determining the palaeoclimate from Lake Baikal over glacial-interglacial cycles. Concentrations (calculated through a 1% Na2CO3 wet-alkaline digestion) at a site in the north basin, however, reveal consistently low values during MIS 3 compared to greater than tenfold changes in diatom concentrations and biovolumes from c. 53.3–51.5 kyr BP. With similar glacial trends present at other low sedimentation sites, we suggest that significant amounts of BSi are removed from diatoms during glacials due to a relative increase in diatom dissolution at the sediment–water interface. This contrasts with existing results from other, higher sedimentation, sites such as those within the Selenga Delta, which display a strong relationship between diatoms and BSi. Site selection is therefore essential when searching for Heinrich and other glacial millennial-scale events in Lake Baikal, and we recommend that both BSi and diatom concentrations be calculated together in future studies.